Reshaping Economic Geography of East Africa : From Regional to Global Integration (Vol. 1 of 2) - World Bank (Washington, DC, 2012)
Five East African countries Burundi, Kenya, Rwanda, Tanzania, and Uganda have made solid progress on integrating regionally in the East African Community (EAC) since 1999. Such advances are crucial, as integration in East Africa has the potential for higher than usual benefits: Burundi, Rwanda, and Uganda are landlocked, with very high costs to their economies. Successful integration will transform the five countries into one coastal, regional economy, slashing such costs. Looking at the East African integration through the lens of economic geography helps to improve sequencing of the integration process and to develop new policies to complement ongoing efforts, maximizing their benefits. Reducing disparities in provision of social services will increase the chances of workers from the inland parts of the EAC to find jobs, especially as administrative obstacles to labor mobility are being removed under the Common Market Protocol. Implementing and deepening the current program of regional infrastructure improvements will ensure that consumers and producers throughout the region are better connected to each other and to global markets. Integration policies facilitating greater economic activity in the coastal areas will help the EAC take advantage of the global demand for manufactured goods and thus to promote employment. That will also generate substantial demand for services and agricultural goods produced inland, amplifying the benefits of the customs union.